Assessing the Impact of Government Policies on Korean SMEs : Innovation, Global Expansion, and Policy Lessons from Germany - Štibraný, Bernard; Sankot, Ondřej, 1988-; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The Master’s Thesis focuses on the SME aspect of innovation policy in the Republic of Korea. It analyses the innovation ecosystem with particular attention to government support, enterprise R&D investment, startup and venture capital development, and the challenges SMEs face in developing their own technologies and commercialising innovation. It also examines SME internationalisation through recent export trends. The final section offers a comparative perspective by assessing key elements of Germany’s SME policy and identifying relevant parallels and lessons for Korea. The thesis finds that the innovation-related goals of the Park and Moon administrations have largely been fulfilled. However, Korean SMEs continue to face significant difficulties, especially after the COVID-19 pandemic. While SME exports have grown in value, their share of total exports is declining, despite what appears to be a shift towards higher value-added sectors. Drawing on German experience, the thesis recommends enhancing vocational training, expanding university–SME internships, strengthening lifelong learning, and introducing intermediary research institutions. It also highlights the need to better tailor digitalisation policies to SME requirements in order to prevent widening of the productivity gap.
Vedoucí práce: Ondřej Sankot
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses